Biomechanical analysis of temporomandibular joints during mandibular protrusion and retraction motions: A 3d finite element simulation. (September 2021) - Feng, Yukai; Shu, Jingheng; Liu, Yang; Zheng, Tinghui; Shao, Bingmei; Liu, Zhan
Highlights: The biomechanical behaviors of temporomandibular joint were investigated. Finite element analysis was used to simulate the biomechanical behaviors. Mandibular protrusion and retraction were recorded using an optical tracking system. Discal stress increased as the condylar displacement increased during the protrusion. Functions described the relationship between stress and condylar displacement. Abstract: Background and Objective: Temporomandibular disorders (TMDs) represent a wide range of musculoskeletal disorders associated with the maxillofacial system, which negatively affect the daily activities of patients. TMD symptoms are caused by the temporomandibular joint (TMJ) overloading. TMJ motions are frequent and can trigger overloading and imbalanced loads on the TMJs, which are assumed to be dangerous. The condyles move forward a lot during mandibular protrusion, which is possibly harmful to the biomechanical environment of the TMJs. The aim of this study was to investigate the biomechanical behavior of TMJs during mandibular protrusion and retraction. Methods: Six three-dimensional maxillofacial system models from asymptomatic subjects were established through computed tomography (CT) and magnetic resonance imaging (MRI). The mandibular protrusion and retraction were recorded using an optical tracking system. Finite element analysis was used to simulate the biomechanical behaviors of the TMJs during the movements. Results: The simulation results were validated to be effective by comparison with the MRIs. The results indicated that the stresses during the protrusion and retraction were approximately equal at the same condylar displacement. Meanwhile the discal stresses, relatively correlated with the condylar displacement, increased as the condylar displacement increased during the protrusion and decreased as the condylar displacement decreased in the retraction. In addition, the average peak maximum and minimum principal stresses of the discs were 0.186 and -0.192 MPa, respectively. Conclusions: The models were reasonable for the investigation of the TMJs motion. Based on the results, three quadratic polynomials were proposed to describe the relationship between the stresses and the condylar displacements. In clinical diagnosis, the functions are helpful in the prediction of the discal stresses by measuring the condylar displacement.